Evolution Science and Ethics in the Third Millennium Challenges and Choices for Humankind - Cliquet, Robert (Springer International Publishing, 2018)
The book aims to revitalise the interdisciplinary debate about evolutionary ethics and substantiate the idea that evolution science can provide a rational and robust framework for understanding morality. It also traces pathways for knowledge-based choices to be made about directions for future long-term biological evolution and cultural development in view of adaptation to the expected, probable and possible future and the ecological sustainability of our planetary environment The authors discuss ethical challenges associated with the major biosocial sources of human variation: individual variation, inter-personal variation, inter-group variation, and inter-generational variation. This book approaches the long-term challenges of the human species in a holistic way. Researchers will find an extensive discussion of the key theoretical scientific aspects of the relationship between evolution and morality. Policy makers will find information that can help them better understand from where we are coming and inspire them to make choices and take actions in a longer-term perspective. The general public will find food for thoughts.